Prevalence of Ocular and Visual Anomalies in Students with Autism Spectrum Disorder (ASD) - Mukhopadhyay, Debapriya; Gogate, Parikshit; Khandekar, Rajiv; Mukherjee, Shreyasi; Mukherjee, Harinath (Archives of Clinical and Medical Case Reports, 2020)
Purpose: To determine the prevalence of ocular and visual anomalies in students with Autism Spectrum Disorder (ASD). Methods: This case-series in 2015-16 included students with ASD of two special schools of Bangalore, India. Comprehensive ocular and vision examination also included accommodation by dynamic retinoscopy and convergence. The amplitude of accommodation was calculated by Hofstetter minimum formula. The accommodative facility was measured by referring to the cycles of accommodative flippers, used ± 2.50D and 14 cycles/min considered as normal. Saccades were tested using Marsden ball movements. Additional eye testing at our institute was with Vision therapy system, ocular motility testing and alternate prism cover test. Result: The 120 students with ASD had a mean age of 12.9 ± 1.7 years. They included autism 58 (48.3%), ASD 27 (22.5%) and other 34 (28.3%). Spectacles correction was needed in 62 (51.7%) students. Refractive error included myopia (57; 92%), hyperopia (5; 8%), myopic astigmatism (3; 4.8%), and mixed astigmatism (2; 3.2%). The compliance of spectacle wear was 12/62 (19.4%) only. Strabismus was seen in 68 (56.7%) students. Accommodative convergence was 4 to 28 mm. Non-accommodative convergence was 4 to 37 mm. Pursuit movements were poor in 35 (29.2%), average in 39 (32.5%), good in 46 (38.3%) students. The saccadic eye movements were good in 100 (83.3%), average in 15 (12.5%) and poor in 5 (4.2%) students. Conclusion: More than half of students with ASD had at least one ocular morbidity. The commonest was refractive errors followed by strabismus. Periodic and comprehensive ocular assessment of autistic students is recommended.